Upaya Guru PAI dalam Membina Akhlak Siswa untuk Mencegah Perilaku Bullyng di Sekolah Dasar - Suriyati Suriyati; Makmur Jaya Nur; Jamaluddin Jamaluddin; Jumrika Jumrika; Rini Zahrah Ramadani (Universitas Muhammadiyah Surabaya, 2026)
This study aims to understand the character and behavior of students, identify forms of bullying, and examine moral development efforts to prevent bullying through Islamic Religious Education (PAI) learning at SDN 257 Gattareng. This study is a qualitative study with the primary data collection technique being interviews. The subjects were PAI teachers who were directly involved in the student character development process. The research findings indicate that overall, the students' character and behavior are good, although there are still relatively mild bullying behaviors, such as teasing, using inappropriate nicknames, and ostracizing peers. Several factors that trigger bullying include a lack of parental attention, the impact of the social environment, and students' emotional instability. Efforts to prevent bullying are carried out through advice, role models from teachers, the integration of moral values ​​into PAI learning, and the implementation of religious activities at school. In addition, collaboration between teachers, the school institution, and parents is very important in building students' character so that they respect each other. With consistent moral development, it is hoped that a safe, comfortable, and bullying-free school atmosphere will be created